A Study on Testing of Random Walk Theory on Indian Capital Markets - Dhuri, Maithili; Burli, Ankita; Chavan, Sumedha (SFIMAR Research Review, 2016)
The efficient market states that the capital market is efficient in processing information. The different forms of efficient market hypothesis have been tested through several empirical studies. The test of weak form hypothesis is essentially tests of whether all information contained in historical prices of securities is fully reflected in current prices. The weak form of Efficient Market Hypothesis (EMH) says that the current prices of stocks already fully reflect all the information that is contained in the historical sequence of prices. The new price movements are completely random. They are produced by new piece of information and are not related or dependent on past price movements. Due to the fluctuations in the stock market, market efficiency denotes that how quickly the market adjusts the newly available information. There is no correlation between the lagged values and thus follow a random walk model. This paper attempts to verify the weak form of market efficiency hypothesis, using auto run test data taken from National Stock Exchange, India. The study span is 2009 to 2016. The present study may help the investors in the making of investment decisions by knowing the form of the market.